A constituição viva: o Supremo Tribunal Federal como moderador das adaptações democráticas no contexto da Constituição de 1988 - Frazão, Hugo Leonardo Abas (2018)
The following dissertation proposes to analyze if it competes to the Supreme Federal Tribunal of Brazil - STF to endorse the modifications of the fundamental values (constitutional compromises) of the constitution of the Federative Republic of Brazil of 1988. It searches to comprehend the role of moderator of the quoted Court in relation to the national politicaldemocratic manifestations producing precedents that recognize, validate and, exceptionally, even create transitions of the constitutional compromises, aiming to represent the evolution of society. The development of this work is by means of a deductive approach that utilizes research of bibliographic reviews. The main objective of this dissertation is to analyze the phenomenon of modification of the constitutional compromises of the Major Law in force in Brazil and the special role of the Supreme Court in this process. Therefore, this work divides in three chapters, each being in charge of reaching a specific goal. The first one is dedicated to the studies of the origins of the judicial constitutionalism by the perspective of the Comparative Law, investigating the possibility of developing a central concept (subjective) for the constitutional justice, dedicated to affirm the preponderance of the legal control regarding the politics control in the ambit of the democratic Countries, in addition to proposing important advancements to the STF as the curator of Brazil’s constitution. The second one proposes to ascertain to which point, nature and degree the constitution allows a political actuation (politicity) of the STF destined to protect achievements originated from the concept of material democracy, such as existing rights already consecrated in the Constitution’s texts and as in relation to the apprehension of “new rights”. The third one investigates the deprecation of the possibility of modifications, followed by the Tribunal, to review the “spirit” of the Brazilian Constitution, under perspective of the Living Constitution Theory, altering constitutional compromises according to the political interests of the society, without, although, to break the legal regimen in force. It specially highlights the STF’s situation towards the majoritarian democracy and the preservation of the immutable clauses (art. 60, §4º, CRFB/88). In this sense, prosecution of the adaptability of the constitutional text to the current social reality happens through the actuation of the Constitutional Tribunal as a reader of the social aspirations, under perspective of the primacies ranked in the Major Law in Force in Brazil